External morphology of the adult Schyzops aegyptiaca aegyptiaca(Lefebvre) - Al Maghrabi, Moftah Suleiman Saeed (Al-Mukhtar Journal of Sciences, 2026)
External morphology of the adult Schyzops aegyptiaca aegyptiaca (Lefebvre) w studied in detail to find out the most important and principal characters of fami Pentatomidae. Many illustration were given to facilitate the recognition of any adi pentatomid species.